Interactions with and activation of immune cells by CD41a+ extracellular vesicles - Tamagne, Marie; Khelfa, Mehdi; Many, Souganya; Neyrinck-Leglantier, Deborah; Delorme, Adèle Silane; Pinheiro, Marion Klea; Andrieu, Muriel; Cleophax, Sabine; Pirenne, France; Vingert, Benoît (Frontiers in Immunology, 2025)
IntroductionThe immunological profiles of CD4+ T lymphocytes (TLs) from patients with hematological malignancies differ between patients who have and have not received transfusions. There may be several reasons for these differences, including the presence of extracellular vesicles (EVs) derived from plasma membrane budding and present in the platelet concentrates. Indeed, EVs can modulate the immune system through interactions with many immune cells, but the underlying mechanisms remain incompletely understood.MethodsWe therefore investigated how interactions with CD41a+ EVs cause immune cells to change phenotype and function. CD41a+ EVs were cultured with TLs, B lymphocytes, and monocytes. Given the potential involvement of monocytes in leukemia progression, we performed a new original multi-omics study to confirm the protein changes and gene activation observed following interaction with CD41a+ EVsResultsThe CD41a+ EVs had immunomodulatory effects on all these cell types but this effect depended on the numbers of EVs. CD4+ TLs required large numbers of CD41a+ EVs for activation, whereas monocytes were the most sensitive. With the new multi-omics technique, we confirmed the direct effects of CD41a+ EVs on protein phenotype and gene activation.ConclusionTransfusion EVs should be considered during the immunological follow-up of patients after transfusion to detect immunological effects on malignant hemopathies, and during the development of new immunotherapies.